Odpowiedź :
Odpowiedź:
a) 2² - √5² = 4 - 5 = -1
c) (4-√2) (4+√2) = 4² - √2² = 16-2 = 14
e) 3² - 2√2² = 9 - √8² = 9-8 = 1
g) 1² - 4√5² = 1 - √80² = 1-80 = -79
Szczegółowe wyjaśnienie:
Odpowiedź:
Szczegółowe wyjaśnienie:
a)
(2 - √5)(2 + √5) = 2² - √5² = 4 - √25 = 4 - 5 = -1
c)
(4 - √2)(√2 + 4) = (4 - √2)(4 + √2) = 4² - √2² = 16 - √4 = 16 - 2 = 14
e)
(3 - 2√2)(3 + 2√2) = 3² - (2√2)² = 9 - (4 * 2) = 9 - 8 = 1
g)
(1 - 4√5)(1 + 4√5) = 1² - (4√5)² = 1 - (16 * 5) = 1 - 80 = - 79
Wykorzystany wzór skróconego mnożenia:
(a - b)(a + b) = a² - b²